2014
DOI: 10.4081/ija.2014.594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crop rotations of rain-fed and irrigated autumn-sown and spring-sown forage on milk feed unit and soil traits in the European Mediterranean environment

Abstract: The aim of this study is to assess the agronomic effect of a threeyear continuous intensive double-crop cultivation of different varieties of legumes and grasses sown in autumn and grasses sown in spring under irrigated and rain-fed conditions in the European Union (EU) Mediterranean environment. Our experiment aimed to compare the dry matter (DM, t ha -1 ) and the milk feed unit (MFU, kg (DM) -1 ) from silage production and soil characteristics of popular autumn-sown Italian ryegrass (Lolium multiflorum Lam.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…Despite the fact, it can be concluded that biomass, yield and yield components can be enhanced significantly by facilitating proper irrigation and legumes and non-legumes forage combination. [43], [44] claimed that in the EU lands, availability of water in the farm decide the success and failure of the crop grown in the farm therefore irrigation should have huge emphasis on irrigation, as conceded with our finding. By contrast, despite adapted varieties that can withstand the critical stress such as drought condition there is immense need of growing different forages in combination to enhance water use efficiency and nutrient uptake [43].…”
Section: H Comparison Of Various Treatment Means On Forage Quality Re...supporting
confidence: 74%
See 1 more Smart Citation
“…Despite the fact, it can be concluded that biomass, yield and yield components can be enhanced significantly by facilitating proper irrigation and legumes and non-legumes forage combination. [43], [44] claimed that in the EU lands, availability of water in the farm decide the success and failure of the crop grown in the farm therefore irrigation should have huge emphasis on irrigation, as conceded with our finding. By contrast, despite adapted varieties that can withstand the critical stress such as drought condition there is immense need of growing different forages in combination to enhance water use efficiency and nutrient uptake [43].…”
Section: H Comparison Of Various Treatment Means On Forage Quality Re...supporting
confidence: 74%
“…[43], [44] claimed that in the EU lands, availability of water in the farm decide the success and failure of the crop grown in the farm therefore irrigation should have huge emphasis on irrigation, as conceded with our finding. By contrast, despite adapted varieties that can withstand the critical stress such as drought condition there is immense need of growing different forages in combination to enhance water use efficiency and nutrient uptake [43]. The superior dry matter production in pure stand of oat and mixtures compared to pure stand of vetch reflects the ability of grass to produce high levels of production.…”
Section: H Comparison Of Various Treatment Means On Forage Quality Re...supporting
confidence: 74%